1990
DOI: 10.1002/jhet.5570270355
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of pyrazolo[3,4‐d]pyrimidine derivatives using ketene dithioacetals

Abstract: The cyclization of 5‐amino‐3‐methylthiopyrazole‐4‐carbonitriles or 4‐carboxamides 3a‐j, which were prepared by the reaction of ketene dithioacetals 1a,b [1a: bis(methylthiomethylenemalononitrile; 1b: bis(methylthio)methylenecyanoacetamide] with hydrazines (hydrazine hydrate, phenylhydrazine, p‐chlorophenylhydrazine, p‐nitrophenylhydrazine), with formamide or carbon disulfide proceeded to give the corresponding 4‐amino‐ or 4‐hydroxy‐3‐methylthiopyrazolo[3,4‐d]pyrimidines 6a‐h in good yields. 3‐Aminopyrazolo[3,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 13 publications
0
50
0
Order By: Relevance
“…The resulting 2(bis(methylthio)methylene)malononitrile was then treated with phenyl hydrazine in absolute ethanol [17]. Cyclization of the 5-amino-3-(methylthio)-1-phenyl-1Hpyrazole-4-carbonitrile (7) by the action of formic acid afforded 3-(methylthio)-1-phenyl-1H-pyrazolo [3,4-d]pyrimidin-4(5H)-one [18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting 2(bis(methylthio)methylene)malononitrile was then treated with phenyl hydrazine in absolute ethanol [17]. Cyclization of the 5-amino-3-(methylthio)-1-phenyl-1Hpyrazole-4-carbonitrile (7) by the action of formic acid afforded 3-(methylthio)-1-phenyl-1H-pyrazolo [3,4-d]pyrimidin-4(5H)-one [18].…”
Section: Resultsmentioning
confidence: 99%
“…Progress of the reactions were monitored by TLC pre-coated with UV fluorescent silica gel and was visualized using UV lamp and different solvent systems as mobile phases. 5-Amino-3-(methylthio)-1-phenyl-1H-pyrazole-4-carbonitrile (7) and 3-(methylthio)-1-phenyl-1H-pyrazolo [3,4-d]pyrimidin-4(5H)-one (8) were prepared according to published method 17 . Compound 9 was obtained following reported procedure [19].…”
Section: Experimental Generalmentioning
confidence: 99%
“…In particular, from comparison of compound 73 with the corresponding C 9 unsubstituted 32 (Table 2), it was shown that the introduction of the small lipophylic methylsulfanyl moiety at C 9 position determined a dramatic shift of binding affinity from hA 3 to the hA 2A subtype, reversing the effect of the ureidic chain at the N 5 position. As depicted in Schemes 1 and 2 the introduction of a substituent at the C 9 position was possible using malononitrile (Scheme 1, a) as the starting material, which, reacting with carbon disulfide and methyliodide in presence of K 2 CO 3 and anhydrous DMF, provided the 2-(bis methylsulfanilmethylene)-malononitrile (b) in good yield [Tominaga et al, 1990]. The subsequent reaction with methylhydrazine in ethanol gave the 1-methyl-3-amino-5-methylsulfanl-4-cyano-pyrazole (c), which was treated, as described in Scheme 1, according to the well-known procedure for the synthesis of the pyrazolo[4,3-e]-1,2,4-triazolo [1,5-c]pyrimidines, previously reported [Baraldi et al, 1996a], to furnish final compounds 76-78, 73.…”
Section: A 3 Adenosine Receptor Antagonistsmentioning
confidence: 99%
“…The usage of many pyrazole derivatives has undoubtedly created considerable attention in developing many different synthetic procedures in pharmaceuticals, agrochemicals, dyestuff. The recent developments in the synthetic routes and the chemistry of pyrazoles have been thoroughly reviewed [1][2][3][4][5]. The condensation of β-enaminonitriles and β-ketoesters with hydrazines continues to be the most widely used method for constructing the aminopyrazoles and pyrazolones, respectively [6,7].…”
Section: Introductionmentioning
confidence: 99%